Kerangka Konsepsual Sistem Pendukung Pengembangan Alternatif Rencana Kota Berbasis Penumbuhan Kreativitas. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
A part of urban planning processes consists of plan-alternative generation, evaluation and selection. Plan-alternative generation activities depend on the capability in creating ideas. The advance itt the computer technology, then, rises a question whether the technology may be employed to support ide generation or creativity needed in the urban planning processes. Discussion in this article shows that it may be done and this article proposes a framework of an idea-generation support system for urban plan alternative generation. This article also proposes a research agenda to build and develop the proposed system.